A Study on FTIR, Antimicrobial, Antioxidant and Hypogycaemic Effect of Diospyros Kaki and Citrullus colocynthis - Hemadri Reddy Salla; Marwah Rashid Humood Al Jahwari; Zeinab Mohammed Rashid Al Tobi (International Journal of Phytomedicine, 2019)
Phytochemical, FTIR screening, Hypoglycemic study, antibacterial, antifungal and antioxidant activity of Citrullus colocynthis and D. kaki fruit were studied. The interest of this study is to evaluate traditional herbal usage to treat many diseases around the sultanate of Oman locally. The functional groups that they contain are (O-H) Phenol, (C-H) Alkyl, (N-H) Amine and (C=C) Alkenyl groups corresponds to their biological phytoconstituents responsible for the medicinal properties. The antibacterial and antifungal activities revealed that all parts of tested samples shown good antimicrobial properties. While leaf of C. colocynthis methanolic extract showed highest zone of inhibition (24.33 mm³) against penicillium. Antioxidant assays were evaluated through DPPH (1, 1- diphenyl-2-picryllhydrazyi) and H2O2 (Hydrogen peroxide scavenging capacity) methods. Peel of D. kaki extract showed higher antioxidant activities than other parts. Antioxidant property of these fruit is due to the presence of significant amount of tannins, phenolic acids and flavonoids on them. A slight change in body weight was observed in all mice compared to the control. All extracts except leaf of C. colocynthis show significant reduction in blood glucose level even more than the positive control which treated with metformin drug. From our investigation of screening different parts of two plants, the results obtained confirm the therapeutic value of both plants used in traditional medicine.